2011
DOI: 10.1007/s11418-011-0520-3
|View full text |Cite
|
Sign up to set email alerts
|

Antinociceptive effects of methyl jasmonate in experimental animals

Abstract: Methyl jasmonate (MJ) is a chemical compound that has been postulated to play a role in plant wound and pathogen responses. While the anti-inflammatory property of MJ has been reported in literature, no studies have been carried out to describe its role in the modulation of pain. Thus, this present investigation sought to evaluate the antinociceptive activity of MJ in animal models of pain. The antinociceptive activity of MJ (10-50 mg/kg) administered intraperitoneally (i.p.) was screened using the acetic acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 25 publications
0
23
0
Order By: Relevance
“…Various studies have shown that JA and MJ do not cause significant toxicity . Umukoro and Abimola reported that, when MJ was administered intraperitoneally in doses ranging from 100 to 500 mg/kg, it was well tolerated by mice and did not produce acute toxic symptoms or death in the animals. Results of several studies on acute toxicity, skin irritation, mucous membrane (eye) irritation, skin sensitization, phototoxicity, and photoallergy of methyl dihydrojasmonate indicated that the LD 50 for oral administration was >5 g/kg, and for skin use, the LD 50 was >2 g/kg.…”
Section: Toxicity Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Various studies have shown that JA and MJ do not cause significant toxicity . Umukoro and Abimola reported that, when MJ was administered intraperitoneally in doses ranging from 100 to 500 mg/kg, it was well tolerated by mice and did not produce acute toxic symptoms or death in the animals. Results of several studies on acute toxicity, skin irritation, mucous membrane (eye) irritation, skin sensitization, phototoxicity, and photoallergy of methyl dihydrojasmonate indicated that the LD 50 for oral administration was >5 g/kg, and for skin use, the LD 50 was >2 g/kg.…”
Section: Toxicity Studiesmentioning
confidence: 99%
“…The first report on jasmonate‐induced anticancer activities exhibited their capacity to cause both cell death and suppression of cell proliferation . Jasmonates are small hydrophobic compounds that act as plant stress hormones and can increase the survival of lymphoma‐bearing animals and humans, and induce death in human leukemia, lung, colon, prostate, neuroblastoma, breast, and melanoma cell lines, as well as in leukemic cells from chronic lymphocytic leukemia (CLL) patients .…”
Section: Biological Activities Of Ja Derivativesmentioning
confidence: 99%
“…), and MeJA (50 mg/kg i.p.) were given daily to the animals for 4 consecutive weeks (Umukoro and Olugbemide, 2011;Lee et al, 2012).…”
Section: Methodsmentioning
confidence: 99%
“…MeJA, been an ubiquitous and naturally occurring plant hormone, is considered to be safe and can be a constituent of human diet via commonly consumed fruits (Cesari et al, 2014). MeJA is known to elicit some pharmacological activities such as antiinflammatory, anti-convulsant, antioxidant, and anti-nociceptive (Umukoro and Olugbemide, 2011;Annafi et al, 2014;Cesari et al, 2014). The in vitro anticancer property of MeJA has been linked to the arrest of cell cycle in human acute lymphoblastic leukemia Molt-4, breast MCF-7 and melanocytic MDA-MB-435, neuroblastoma BE(2)-C, cervical carcinoma, and HeLa cells (Jiang et al, 2008;Yeruva et al, 2008;Zhang and Xing, 2008;Zhao et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The stimulus was applied to the plantar surface of the left hind paw by increasing the pressure until the rat withdrew its limb, which was considered the threshold. 27 The threshold value at each time point was considered the mechanical nociceptive threshold. A minimum of 5 min was allowed between consecutive measures.…”
Section: Randall-selitto Testmentioning
confidence: 99%